A novel system to culture human intestinal organoids under physiological oxygen content to study microbial-host interaction. - Tatiana Y Fofanova; Umesh C Karandikar; Jennifer M Auchtung; Reid L Wilson; Antonio J Valentin; Robert A Britton; K Jane Grande-Allen; Mary K Estes; Kristi Hoffman; Sashirekha Ramani; Christopher J Stewart; Joseph F Petrosino (PLoS ONE, 2024)
Mechanistic investigation of host-microbe interactions in the human gut are hindered by difficulty of co-culturing microbes with intestinal epithelial cells. On one hand the gut bacteria are a mix of facultative, aerotolerant or obligate anaerobes, while the intestinal epithelium requires oxygen for growth and function. Thus, a coculture system that can recreate these contrasting oxygen requirements is critical step towards our understanding microbial-host interactions in the human gut. Here, we demonstrate Intestinal Organoid Physoxic Coculture (IOPC) system, a simple and cost-effective method for coculturing anaerobic intestinal bacteria with human intestinal organoids (HIOs). Using commensal anaerobes with varying degrees of oxygen tolerance, such as nano-aerobe Bacteroides thetaiotaomicron and strict anaerobe Blautia sp., we demonstrate that IOPC can successfully support 24-48 hours HIO-microbe coculture. The IOPC recapitulates the contrasting oxygen conditions across the intestinal epithelium seen in vivo. The IOPC cultured HIOs showed increased barrier integrity, and induced expression of immunomodulatory genes. A transcriptomic analysis suggests that HIOs from different donors show differences in the magnitude of their response to coculture with anaerobic bacteria. Thus, the IOPC system provides a robust coculture setup for investigating host-microbe interactions in complex, patient-derived intestinal tissues, that can facilitate the study of mechanisms underlying the role of the microbiome in health and disease.